(untitled) (lentera, 2020)
In general, the objectives of improving learning to be achieved from this activity are: improving early childhood learning outcomes, improving early childhood language skills, improving children’s abilities in language activities, training children’s thinking skills logically and systematically and developing children’s abilities in utilizing various media learning. This learning improvement is a type of classroom action research that includes planning, action, observation, and reflection. The subjects of this study were 15 students of RA As Salam in group B-I consisting of 5 boys and 10 girls with the theme developed was the plant theme. The object of this research is children’s activities to find out how enthusiastic students are in recognizing letters through letter cards media. The results obtained in the ability to recognize letters have increased. Before the action was taken, the level of the ability to recognize letters was still very low, after the first cycle class research was carried out it gained 44% and in the second cycle it increased to 80%. After conducting research starting from pre-cycle, cycle I and cycle II, it was concluded that the ability to recognize letters of the B-I RA As Salam group children had increased through the use of letter cards media.